(untitled) (Świat Idei i Polityki, 2014)
This article is an attempt of redefinition of the term *war” by comparison of its former and contemporary meanings. It contains a summary of the two fundamental works describing conflicts, i.e. The Art of War by Sun Tzu and The War treaty by Carl von Clausewitz. In the first case, attention to a philosophic attitude to a war has been paid by expression of belief that the most effective victory is when held without fighting. In the second case, the most interesting parts of the tract and analogies to real military conflicts have been displayed. In the second part of this work, a contemporary meaning of the term *war”, especially so called asymmetric conflicts, has been discussed. The author tried to underline that in such conflict one of its participants is usually not prepared to the way of fighting used by the other one. This problem has been analysed in accordance with the thoughts of Sun Tzu and Carl von Clausewitz.